Notice of various attempts which have been made to Read and Interpret the Inscription on the Newton Stone, Garioch, Aberdeenshire (Proceedings of the Society of Antiquaries of Scotland, 1865)
The author collates attempted translations of the inscription found on the Newton Stone that he requested from scholars across Europe. He begins with a brief description of the stone and its inscription. When describing the various interpretations of the inscription, the author includes the schoalr’s methodology, assumptions and conclusions.